2000
DOI: 10.2355/isijinternational.40.182
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Calculations of Phase Equilibria in the Fe-Cr-S System.

Abstract: Phase equilibria in the Fe-Cr-S system were analyzed on the basis of the thermodynamic evaluation of the Fe-FeS, Fe-Cr, Cr-CrS and Fe-FeS-CrS-Cr systems. The Gibbs energy of individual phase was approximated by the two sub-lattice model for describing the thermodynamic properties. Most of the experimental information was well described by the present set of thermodynamic parameters. In particular, the calculated liquidus surface in the Fe-rich portion and the solubilities of S in the fcc and the bcc phases wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 18 publications
0
23
0
3
Order By: Relevance
“…According to the phase diagram, the maximum solubility limit of S in Fe at 1473 K is 310 ppm in mass% units. Furthermore, from thermodynamic calculations, 8) the solubility limit of S was estimated to be about 270 ppm in a Fe-10Cr alloy at 1473 K. The S content in the S-doped steel was 150 ppm as shown in Table 1, and hence a complete solid solution of S could be Table 2, sulfide would be formed or S would segregate in the grain boundary, because the solubility limit of S was estimated to be null at 873 K. 7,8) Furthermore, to exclude the effect of the matrix structures on the steam oxidation resistance, the martensitic structure should be maintained in the specimen even after tempering. So, the tempering temperature was set at 873 K, a temperature low enough to prevent the microstructural evolution from the martensite phase to the ferrite phase.…”
Section: Selection Of S Contentmentioning
confidence: 99%
“…According to the phase diagram, the maximum solubility limit of S in Fe at 1473 K is 310 ppm in mass% units. Furthermore, from thermodynamic calculations, 8) the solubility limit of S was estimated to be about 270 ppm in a Fe-10Cr alloy at 1473 K. The S content in the S-doped steel was 150 ppm as shown in Table 1, and hence a complete solid solution of S could be Table 2, sulfide would be formed or S would segregate in the grain boundary, because the solubility limit of S was estimated to be null at 873 K. 7,8) Furthermore, to exclude the effect of the matrix structures on the steam oxidation resistance, the martensitic structure should be maintained in the specimen even after tempering. So, the tempering temperature was set at 873 K, a temperature low enough to prevent the microstructural evolution from the martensite phase to the ferrite phase.…”
Section: Selection Of S Contentmentioning
confidence: 99%
“…1, it has been reported that metal-sulfide pseudobinary systems such as Fe-MnS and Cr-CrS often show a two-phase liquid region in the liquid field. [20][21][22][23][24][25]39) In Fe-Mn-S alloys, for instance, when the concentration of S in the liquid phase is 21 wt% at 1 370°C, the S-rich and the Fe-rich liquid phases as well as and solid MnS will appear. 24) Changes in the mass fraction of S in the liquid were estimated employing the Brody-Flemings model on the assumptions mentioned previously.…”
Section: A Comparison Of the Alloys 1-5mentioning
confidence: 99%
“…There have also been reports on the improvement of corrosion resistance resulting from the decreasing Mn/S ratio in stainless steel consequent with increasing Cr content in sulfide. [7][8][9] The present work is one of a series of systematic studies [9][10][11][16][17][18][19][20][21][22] on the phase equilibria and the morphology of various sulfides in metals, which focuses on the microstructural features of CrS in the Fe-Cr-S ternary system. In particular, a confocal scanning laser microscope (CSLM) with infrared image furnace was utilized for direct investigation of the microstructure at high temperature.…”
Section: Introductionmentioning
confidence: 99%